Mutations in the rpoB Gene of Multidrug-Resistant Mycobacterium tuberculosis Isolates from China - Yue, Jun (American Society for Microbiology, 2003)
Mutations in the 81-bp rifampin resistance determining region (RRDR) and mutation V176F locating at the beginning of the ropB gene were analyzed by DNA sequencing of 86 Mycobacterium tuberculosis clinical isolates (72 resistant and 14 sensitive) from different parts of China. Sixty-five mutations of 22 distinct kinds, 21 point mutations, and 1 insertion were found in 65 of 72 resistant isolates. The most common mutations were in codons 531 (41%), 526 (40%), and 516 (4%). Mutations were not found in seven (10%) of the resistant isolates. Six new alleles within the RRDR, along with five novel mutations outside the RRDR, are reported. None of isolates contained the V176 mutation.